Teacher Communication Patterns in the Teaching and Learning Process of Elementary School Students - Harilama, Stefi H.; Kawung, Eveline J.R.; Tangkudung, Joane P.M. (Journal La Edusci, 2022)
The purpose of this study is to examine the role of teachers' communication styles in the education of elementary school pupils on Lembeh Island, Bitung City. This study employs a phenomenological qualitative methodology. Purposive sampling was used to identify primary school teachers on Lembeh Island as study participants. The researchers used observation, in-depth interviews, and document studies to gather data. Reducing data, displaying data for verification, and generating conclusions were all steps in the data analysis process. Triangulation was used to check the data for authenticity. According to the study's findings, two-way communication (Two-Way Communication) between educators on the Lembeh Islands's teaching staff and their students is a transactional communication pattern facilitated by the humanistic process and aimed at facilitating the sharing of information and the development of mutual understanding through the use of a unified curriculum.